2018
DOI: 10.1111/odi.12762
|View full text |Cite
|
Sign up to set email alerts
|

The medically compromised patient: Are dental implants a feasible option?

Abstract: In healthy subjects, dental implants have evolved to be a common therapy to solve problems related to stability and retention of dentures as well as to replace failing teeth. Although dental implants are applied in medically compromised patients, it is often not well known whether this therapy is also feasible in these patients, whether the risk of implant failure and developing peri-implantitis is increased, and what specific preventive measures, if any, have to be taken when applying dental implants in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 62 publications
0
44
0
7
Order By: Relevance
“…Implant treatment in the medically compromised patient represents, nowadays, a common clinical situation for dentists and MetS prevalence has been constantly rising in the last years, involving ≈30% of the population …”
Section: Discussionmentioning
confidence: 99%
“…Implant treatment in the medically compromised patient represents, nowadays, a common clinical situation for dentists and MetS prevalence has been constantly rising in the last years, involving ≈30% of the population …”
Section: Discussionmentioning
confidence: 99%
“…That is, to begin to fully and appropriately operationalize implant therapy for medically compromised patients, we will need not only to continue to challenge existing dogma and fully define the long-term risks, but will also need to understand the benefits gained from implant therapy as an important contribution to improved oral and systemic health. 97,105,106 It is perhaps one of the more subtle contributions from these earlier studies challenging the longstanding implications for diabetes in implant therapy that it has taken forward similar considerations across a range of systemic conditions. 98,103,105 Going forward, there is a clear trend of newer studies offering more stringent scientific documentation of the impact of diabetes and glycemic status on implant survival, with many of these studies finding positive results for implant integration and survival.…”
Section: Number Of Included Studies Study Conclusionmentioning
confidence: 99%
“…She would make removable partial denture because there was no other solution, there was no point in doing it [the implant] because I had taken alendronate for several years and this would cause necrosis; there was no solution. (Respondent 12) It was observed that there is no consensus in the literature on contraindications for implant surgery in systemicallyimpaired patients, mainly due to the lack of randomized clinical studies (Lopez-cedrun et al, 2013;Manor, Oubaid, Mardinger, Chaushu, & Nissan, 2009;Guobis, Pacauskiene, & Astramskaite, 2016;Vissink, Spijkervet, & Raghoebar, 2018).…”
Section: Was Afraid Of Rejection By My Body Because Of Cigarette Ymentioning
confidence: 99%